Constructing Hamiltonian quantum theories from path integrals in a diffeomorphism-invariant context - Ashtekar, Abhay; Marolf, Donald; Mourao, José Manuel; Thiemann, Thomas (Classical and Quantum Gravity, 2000)
Osterwalder and Schrader introduced a procedure to obtain a (Lorentzian) Hamiltonian quantum theory starting from a measure on the space of (Euclidean) histories of a scalar quantum field. In this paper, we extend that construction to more general theories which do not refer to any background, spacetime metric (and in which the space of histories does not admit a natural linear structure). Examples include certain gauge theories, topological field theories and relativistic gravitational theories. The treatment is self-contained in the sense that an a priori knowledge of the Osterwalder-Schrader theorem is not assumed.